Comparison of Bright Band Radar from GPM and MRR Observation in West Sumatera - Ramadhan, Ravidho; Marzuki, Marzuki; Vonnisa, Mutya; Harmadi, Harmadi; Hashiguchi, Hiroyuki; Shimomai, Toyoshi (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2021)
The Bright band (BB) observation can be used as an indication of the melting layer height. Measurement of BB from Normal Scan (NS) on Global Precipitation Measurement (GPM) had been compared with Micro Rain Radar (MRR), which is installed in Kototabang, West Sumatera (0.23° S; 100.32°E; 865 m above sea level). The GPM data were collected from December 2014 to June 2018 and compared with MRR observation from January 2012 to August 2016. The BB values from these instruments were compared with those recommended by the International Telecommunication Union Recommendation (ITU-R) P.839. The BB from GPM and MRR showed slightly diurnal and seasonal variations. BB observations from GPM and MRR show good agreement with slight diurnal and seasonal variations differences. BB observations are more similar when the intensity of solar radiation is lower, i.e., at night (18.00-24.00 LT) until early morning (00.00-06.00 LT). Furthermore, MRR showed a slight bimodal pattern in the seasonal variation, while GPM did not. Thus, the seasonal variation in the observation of both instruments is different. The most significant difference from the seasonal variation was observed in the summer season (June-August (JJA)). The mean BB of the two instruments is lower than the Freezing Height Level (FHL) value calculated from the ITU-R model. However, many BB from the two instruments (>36 %) have a BB altitude higher than FHL. Thus, the constant assumption of FHL in West Sumatera for the rain attenuation estimation of microwaves may not be appropriate.